2018
DOI: 10.1080/1028415x.2018.1466513
|View full text |Cite
|
Sign up to set email alerts
|

The ethanolic extract obtained fromCampomanesia pubescens(D.C.) O.BERG fruits exerts anxiolytic and antidepressant effects on chronic mild stress model and on anxiety models in Wistar rats: Behavioral evidences

Abstract: The chemical analysis of the EEFCP indicated high content of flavonoids and the behavioral analysis revealed an antidepressant and anxiolytic effect, suggesting that these phytochemicals may be involved with these actions in the CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…Regarding emerging therapeutic treatments, subacute and chronic ketamine treatment was demonstrated to have antidepressant, anxiolytic, and precognitive effects by means of the CMS model with great reliability in 2017 [52]. Several drugs, including ginsenoside Rg2, ethanolic extract of Capsicum pubescens fruits (EEFCP), icariin, and lurasidone, have been shown to exert a similar antidepressive action in the past five years [53,54,55,56].…”
Section: Depression Modeling Approachesmentioning
confidence: 99%
“…Regarding emerging therapeutic treatments, subacute and chronic ketamine treatment was demonstrated to have antidepressant, anxiolytic, and precognitive effects by means of the CMS model with great reliability in 2017 [52]. Several drugs, including ginsenoside Rg2, ethanolic extract of Capsicum pubescens fruits (EEFCP), icariin, and lurasidone, have been shown to exert a similar antidepressive action in the past five years [53,54,55,56].…”
Section: Depression Modeling Approachesmentioning
confidence: 99%
“…It is important to note that chemically synthesized drugs are generally improved derivatives of prototypes of herbal isolated drugs [6]. Moreover, it has been observed that medicinal plants or extracts, used as co-adjuvant or as alternate therapy to allopathic medicine, are effective and have few adverse effects, as well as being low cost and locally available [7]. Flavonoids are ubiquitous plant secondary metabolites found in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Each stress stimulus was discontinuous and irregular. Administration of Andro/fluoxetine/K252a/vehicle was performed daily during the final 2 weeks (Zu et al, 2017; Sanna et al, 2018; Villas Boas et al, 2018; Wang et al, 2018). To assess the depressive-like behaviors of mice, the FST, TST, and SPT were performed.…”
Section: Methodsmentioning
confidence: 99%